2016
DOI: 10.1177/0954407016674606
|View full text |Cite
|
Sign up to set email alerts
|

A review of evaporative cooling system concepts for engine thermal management in motor vehicles

Abstract: The evaporative cooling system concepts proposed over the past century for engine thermal management in automotive applications are examined and critically reviewed. The purposes of this review are to establish the evident system shortcomings and to identify the remaining research questions that need to be addressed to enable this important technology to be adopted by vehicle manufacturers. Initially, the benefits of the evaporative cooling systems are restated in terms of the improved engine efficiency, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…Hence on this basis, the researchers will focus on analyzing the impact of modifications to the seawater cooling system on a diesel motor as a driving force for traditional fishing boats. In general, a closed cooling system is a system which comprises of a diesel motor equipped with a hopper, where the engine cylinder block is surrounded by seawater [12], as seen in Figure 4. When the diesel motor is being operated, the seawater in the hopper boils, causing the seawater to evaporate, which at the same time causes the volume of seawater to decrease.…”
Section: Experiments With Adding Valvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence on this basis, the researchers will focus on analyzing the impact of modifications to the seawater cooling system on a diesel motor as a driving force for traditional fishing boats. In general, a closed cooling system is a system which comprises of a diesel motor equipped with a hopper, where the engine cylinder block is surrounded by seawater [12], as seen in Figure 4. When the diesel motor is being operated, the seawater in the hopper boils, causing the seawater to evaporate, which at the same time causes the volume of seawater to decrease.…”
Section: Experiments With Adding Valvesmentioning
confidence: 99%
“…Figure 4. Evaporative Cooling System in which the Engine Cylinder Block Is Surrounded by a Bath of Water (Hopper) [12]…”
Section: Experiments With Adding Valvesmentioning
confidence: 99%
“…The natural and forced cooling application and its effectiveness are highlighted for motor vehicle applications through numerical simulations and these are compared with evaporative boiling phase cooling mechanism. The outcome of the studies from Jafari et al [1] concludes the vapour bubble formation at solid-liquid interaction separates it from the process of evaporation at liquid-vapour boundary. The boiling jet impingement studies to cool high power electronics are shown on unit area of heat source and developed non-dimensional heat transfer relation through sensitivity parameters like nozzle diameter, nozzle to source surface spacing, jet velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Bilindiği üzere motorlarda yakıt enerjisinin üçte biri soğutma sistemiyle dışarı atılmaktadır (John 1988). Bununla birlikte optimal termal yönetim sistemi için model tabanlı kontrol stratejilerinin uygulanması umut verici bir yaklaşım olmasına rağmen henüz gerekli ilgiyi görmemiştir (Jafari et al, 2016;Tao and Wagner, 2016). Bu durumun ana nedeni, geleneksel içten yanmalı motor soğutma sistemlerinde kullanılan pompa, mum termostat ve fan gibi bileşenlerinin pasif yapıda olup çalışmaları değişken motor çalışma koşullarına göre ayarlanamamaktadır .…”
Section: Introductionunclassified